Probing the Interaction of Nucleobases and Fluorophore‐Tagged Nucleobases with Graphene Surface: Adsorption and Fluorescence Studies. Issue 11 (17th March 2020) - Bhai, Surjit; Ganguly, Bishwajit
Abstract: Adsorption of a fluorophore‐labeled DNA oligonucleotide by graphene nano‐probes is of interest to exploit as bio‐sensing material. This work reports the fluorescence properties of fluorophore tagged nucleobases on the graphene surface computationally. The interaction of nucleobases and fluorophore tagged nucleobases to the graphene surface examined using M062X/6‐31G(d) level of theory in the gas phase and ethanol solvent. The binding energies of nucleobases on the graphene surface in the gas phase follows the order: G>A≥C≥T in agreement with the previous reports. The slab model calculations performed with LDA/PWC/DND level of theory also revealed a similar binding affinity on the graphene surface in the gas phase. The fluorescence of benzoxazole as fluorophore tagged with nucleobase on graphene surface was investigated using TD‐DFT M06‐2X/6‐31G(d) level of theory. The binding preference of the fluorophore tagged nucleobases is not significantly different in ethanol solvent. The aromaticity of the nucleobases tagged fluorophore on the graphene surface was investigated by NICS (1) and NICS (1)zz calculations and the aromaticity was found to be increased upon interaction with the graphene surface. The fluorescence quenching upon binding of fluorophore tagged nucleobases on graphene surface revealed the importance of purine nucleobases and found to be more prominent with guanine tagged fluorophore. Abstract : The quantum yield of fluorophore attached to the nucleic acids is dependent on many factors and one of these is the appropriate choice of bases lies adjacent to the fluorescent molecules. The graphene monolayer has been chosen as a probe. The computational results unravel the emission phenomena is largely influenced by purine bases in comparison to their pyrimidine analogs. The fluorescence quenching is more prominent with guanine tagged fluorophore with a graphene surface.